Ultra-narrow band gap electron acceptor, active layer and organic solar cell
Ultra-narrow bandgap electron acceptors with benzothiadiazole ladder-shaped structures address energy level matching issues, enhancing near-infrared absorption and stability, resulting in high-efficiency organic solar cells.
Patent Information
- Application Number
- CN202411281356.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-12
AI Technical Summary
Existing ultra-narrow bandgap electron acceptors in organic solar cells face challenges in matching energy levels with wide bandgap polymer donors, leading to poor photo-oxidation resistance and intrinsic stability, limiting power conversion efficiency and application scenarios.
Development of ultra-narrow bandgap electron acceptors with symmetrical or asymmetric benzothiadiazole ladder-shaped fused ring structures, enhanced by benzothiadiazole derivative ends or cyanoindanone terminals, to improve electron-withdrawing ability and intramolecular charge transfer, paired with wide bandgap polymer donors in an active layer.
The enhanced electron acceptors expand near-infrared absorption, improve photoelectric conversion efficiency, and enhance device stability, achieving high power conversion efficiency and light transmittance in semi-transparent solar cells.
Smart Images

Figure CN119192201A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of organic photovoltaic technology, and in particular to an ultra-narrow bandgap electron acceptor, an active layer and an organic solar cell. Background Art
[0002] Organic solar cells (OSCs) have the potential for diverse application scenarios due to their advantages such as light weight, translucency and mechanical flexibility. Among them, the development of active layer materials with near-infrared absorption ability is the key to promoting the performance improvement and application expansion of OSCs. In the early era when fullerene acceptors were the main ones, most of the research focused on designing donor materials with near-infrared absorption. With the rise of non-fullerene acceptors, such as acceptor-donor-acceptor (ADA) type fused ring acceptors IEIC or ITIC and A-DA'DA type trapezoidal fused ring acceptor Y6, the absorption spectrum of acceptor materials has been effectively expanded, greatly improving the utilization of the solar spectrum and the generation of photocurrent by OSCs, thereby rapidly increasing the power conversion efficiency (PCE) in recent years. At the same time, some electronic acceptor materials with ultra-narrow band gaps (band gaps less than 1.3 eV) have also appeared one after another. Ultra-narrow band gap electronic acceptor materials have broad application prospects and scientific value in the fields of semi-transparent organic photovoltaics, stacked organic photovoltaics, and organic photodetectors.
[0003] To construct ultra-narrow bandgap electron acceptors with near-infrared absorption, the most effective strategy is to enhance the intramolecular charge transfer effect, that is, to enhance the electron-pushing ability of the electron-donating unit (D unit) or to enhance the electron-pulling ability of the electron-withdrawing unit (A unit). Reference 1 (Jianhui Hou, Huifeng Yao. Design, Synthesis, and Photovoltaic Characterization of a Small Molecular Acceptor with an Ultra-Narrow Band Gap. Angew. Chem. Int. Ed. 56, 3045-3049, 2017, doi: 10.1002 / anie.201610944) discloses an ADA-type ultra-narrow band gap receptor IEICO-4F developed by introducing an alkoxy side chain into the D unit and a fluorine atom into the A unit on the basic structure of the ADA-type fused ring receptor IEIC, which achieves an absorption band edge of nearly 1000 nm (optical band gap of 1.24 eV), but the PCE of the binary OSC is only 10.0%, which lags behind the first-class PCE in the OSC field.
[0004] Reference 2 (Xiaozhang Zhu, Wuyue Liu, Theory-Guided Material Design Enabling High-Performance Multifunctional Semitransparent Organic Photovoltaics without Optical Modulations, Adv. Mater, 34, 2200337, 2022, doi: 10.1002 / adma.202200337) discloses an A-DA'DA type ultra-narrow band gap electron acceptor ATT-9, which is achieved by inserting a quinone-type thiophene π bridge between the central core and the end of the electron acceptor. Its absorption band edge is 1075nm, the optical band gap is 1.15eV, and the PCE of the binary OSC is only 13.4%, which lags behind the first-class PCE in the OSC field.
[0005] The ultra-narrow bandgap electron acceptors obtained by enhancing the electron donating ability of the D unit usually have a higher HOMO energy level, which determines that they are difficult to match with commonly used high-performance wide bandgap polymer donors (such as PM6, D18, etc.), and their anti-photooxidation ability and intrinsic stability are relatively poor. The device performance lags far behind the first-class efficiency in the field of binary OSCs. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides an ultra-narrow bandgap electron acceptor, which is constructed by enhancing the electron-withdrawing ability of the electron acceptor, and can match the energy level of the wide bandgap polymer electron donor to improve the photo-oxidation resistance.
[0007] An ultra-narrow bandgap electron acceptor, comprising a symmetrical acceptor with a benzothiadiazole ladder-shaped fused ring structure as the core and both ends being benzothiadiazole derivative ends, and the specific structural formula is as follows:
[0008]
[0009] Where R1 is C4-C 30 A branched or straight alkyl chain, R2 is C4-C 30 branched or straight alkyl / alkoxy chains;
[0010] Alternatively, an ultra-narrow bandgap electron acceptor includes an asymmetric acceptor with a benzothiadiazole ladder-shaped fused ring structure as the core, a benzothiadiazole derivative terminal at one end, and a cyanoindanone terminal at the other end, and the specific structural formula is as follows:
[0011]
[0012] Where R1 is C4-C30 A branched or straight alkyl chain, R2 is C4-C 30 branched or straight alkyl / alkoxy chains.
[0013] Preferably, the terminal A of the cyanoindanone is at least one of the following chemical structural formulas:
[0014]
[0015] Both the terminal ends of benzothiadiazole derivatives and cyanoindanones have super strong electron-withdrawing ability, which greatly enhances the intramolecular charge transfer effect, thereby expanding the absorption of the molecule in the near-infrared region.
[0016] The present invention develops a terminal with super strong electron-withdrawing ability and constructs an ultra-narrow bandgap electron acceptor, which can improve the photoelectric conversion efficiency and stability of the device and improve the application scenarios of the device.
[0017] In order to solve the problem of poor intrinsic stability of the electron acceptor, the present invention also provides an active layer.
[0018] An active layer is formed by blending an electron acceptor and an electron donor into a film, wherein the electron donor is a wide band gap polymer donor material, and the wide band gap polymer donor material is at least one of the following chemical structural formulas:
[0019]
[0020] The electron acceptor is the ultra-narrow band gap electron acceptor described in the present invention.
[0021] The present invention uses a wide bandgap polymer donor material to match an ultra-narrow bandgap electron acceptor, so that the absorption spectrum range of the active layer can be fully covered from the visible region to the near-infrared region.
[0022] Preferably, the weight ratio of the electron donor to the electron acceptor in the active layer is 1:2 to 2:1, and the thickness of the active layer is 50 to 300 nm.
[0023] The ratio of electron donors to electron acceptors in the active layer affects the crystallinity of the active layer, and thus affects the blended morphology of the active layer. Adjusting the ratio of electron donors to electron acceptors and the thickness of the active layer within a certain range can make the active layer have better crystallinity, regulate the absorption intensity of different regions, optimize the morphology of the blended film, and improve the energy conversion efficiency of organic solar cells.
[0024] The present invention also provides a method for preparing the active layer, which is prepared by forming a mixed solution of an electron acceptor, an electron donor and an additive into a film and then subjecting the film to annealing treatment.
[0025] Preferably, the additive in the film-forming process is 1,8-diiodooctane or chloronaphthalene, and the volume of the additive is 0.1-5% of the volume of the mixed solution of the electron acceptor and the electron donor.
[0026] The additives are used to induce crystallization of the donor and acceptor materials so that the active layer has better crystallinity.
[0027] Preferably, the annealing temperature during the annealing treatment is 80-200° C., and the annealing time is 5-30 min.
[0028] Appropriate annealing of the active layer can improve the crystallinity of the active layer, facilitate the transport of photogenerated carriers, and enhance the photocurrent generation of the device.
[0029] The present invention also provides an organic solar cell, comprising a substrate, an anode, an anode modification layer, an active layer, a cathode modification layer, and a cathode.
[0030] Preferably, glass is used as the substrate; ITO or FTO is used as the anode; 2PACz, PEDOT:PSS or MoO3 is used as the anode modification layer; PDINN, PFN-Br or ZnO is used as the cathode modification layer; and Ag is used as the cathode.
[0031] The present invention selects substrates and electrodes with high transmittance and good conductivity to improve the energy conversion efficiency of the device and reduce the resistivity of the solar cell. In addition, by introducing an interface modification layer between the active layer and the electrode, the energy level arrangement between the donor and the acceptor and the electrode can be adjusted, a single carrier transport layer can be formed, the interface morphology can be modified, and the electric field in the device can be regulated.
[0032] Preferably, PM6 or D18 is used as the electron donor; BTC-1, BTC-2 or BTC-3 is used as the electron acceptor. The specific chemical structure of the electron acceptor is as follows:
[0033]
[0034] The present invention selects the electron donor PM6 or D18 and the electron acceptor BTC-1, BTC-2 or BTC-3 to form an active layer, which can solve the problems of energy level matching and poor stability.
[0035] Preferably, the thickness of the cathode Ag is 10 nm to 100 nm, and an optical layer of TeO2 is modified on the cathode Ag.
[0036] The present invention reduces the cathode thickness of the organic solar cell and modifies the optical layer TeO2, which can be assembled into a semi-transparent organic solar cell, thereby improving the light transmittance and light utilization rate of the device while maintaining high energy conversion efficiency.
[0037] The beneficial effects of the present invention are:
[0038] (1) The present invention obtains symmetrical or asymmetrical electron acceptors by introducing one or two benzothiadiazole derivative ends, thereby enhancing the intramolecular charge transfer effect and expanding the absorption of the electron acceptors in the near-infrared region. Among them, the symmetrical acceptor BTC-2 obtained by introducing two benzothiadiazole derivative ends has an absorption band edge significantly extended to about 1000nm, a corresponding optical band gap of 1.24eV, and a deeper HOMO energy level.
[0039] (2) The preparation method of the active layer provided by the present invention is simple in process and short in time.
[0040] (3) The active layer formed by the blending of the electron donor and the electron acceptor in the present invention broadens the range of the absorption spectrum and is beneficial to the transport of photogenerated carriers.
[0041] (4) The binary organic solar cell PM6:BTC-2 assembled based on the electron donor PM6 and the electron acceptor BTC-2 has high energy conversion efficiency (PCE) and high short-circuit current density, achieving the highest PCE and the highest short-circuit current density of binary organic solar cell devices based on ultra-narrow bandgap electron acceptors.
[0042] (5) The binary semi-transparent organic solar cell PM6:BTC-2 assembled based on the electron donor PM6 and the electron acceptor BTC-2 has a high PCE, high average light transmittance (APT) and high light utilization efficiency (LUE), achieving the highest LUE of binary semi-transparent organic solar cell devices to date. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 It is a synthetic route for the electron acceptors BTC-1, BTC-2 and BTC-3 at the terminal of benzothiadiazole derivatives.
[0044] Figure 2 It is the chemical structure formula of BTC-1, BTC-2 and BTC-3.
[0045] Figure 3 It is the cyclic voltammetry test curve of BTC-1, BTC-2 and BTC-3.
[0046] Figure 4 It is the UV-visible absorption spectra of BTC-1, BTC-2 and BTC-3 in the thin film state.
[0047] Figure 5 It is the current-voltage curve of the binary organic solar cell under light.
[0048] Figure 6The current-voltage curve of a binary semi-transparent organic solar cell under illumination is obtained by regulating the Ag electrode and the optical layer.
[0049] Figure 7 This is the current-voltage curve of a binary semi-transparent organic solar cell under illumination obtained by adjusting the ratio of electron acceptors. DETAILED DESCRIPTION
[0050] The specific implementation of the present invention is further described in detail below with reference to the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are any processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art.
[0051] Example 1
[0052] The polymer electron donor PM6 involved in the present invention is a commercial product and can be purchased from a manufacturer (manufacturer: Shuolun Organic Optoelectronics Technology (Beijing) Co., Ltd.; CAS No. (PM6): 1802013-83-7). The terminal of the benzothiadiazole derivative is a newly developed material of the present invention. By connecting the benzothiadiazole ladder-shaped fused ring core and the terminal through a one-step or two-step Knoevenagel reaction, a symmetrical or asymmetrical electron acceptor based on the terminal of the benzothiadiazole derivative can be obtained.
[0053] The following provides three specific preparation methods of electron acceptors based on the terminal of benzothiadiazole derivatives, namely BTC-1, BTC-2, and BTC-3. The specific synthesis routes are as follows: Figure 1 As shown (wherein, compounds 1, 7, 9, and 10 are commercial products, all purchased from manufacturers. Compound 1 was purchased from: Shanghai Bid Pharmaceutical Technology Co., Ltd.; CAS number: 129365-93-1; Compound 7 was purchased from: Shenzhen Ruixun Optoelectronic Material Technology Co., Ltd.; item number: TPB76; Compound 9 was purchased from: Shenzhen Ruixun Optoelectronic Material Technology Co., Ltd., corresponding to CAS number: 2197167-50-1; Compound 10 was purchased from: Shenzhen Ruixun Optoelectronic Material Technology Co., Ltd., corresponding to CAS number: 2083617-82-5).
[0054] The specific synthesis steps of BTC-1, BTC-2 and BTC-3 are as follows:
[0055] (1) Synthesis of Compound 2
[0056] Compound 1 (5.0 g, 31.6 mmol), dichloromethane (30 mL), and triethylamine (30 mL) were added to a round-bottom flask. SOCl2 (25 mL, 344 mmol) and CH2Cl2 (25 mL) were slowly added dropwise in an ice-water bath to form a mixed solution. After the mixed solution was stirred at 50 °C for 5 hours, a saturated aqueous solution of Na2CO3 was added and stirred for 15 minutes. The mixture was filtered and the filtrate was extracted with dichloromethane. After removing the solvent, the mixture was purified by column (eluent was petroleum ether: dichloromethane = 1:4, v / v) to obtain a light yellow solid (4.73 g, yield 80.4%), which was compound 2.
[0057] The molecular structure of compound 2 was determined using a nuclear magnetic resonance spectrometer, specifically including: dissolving compound 2 in deuterated chloroform (CDCl3) and filling it into a nuclear magnetic resonance tube for testing. The results are as follows:
[0058] 1 H NMR (400MHz, CDCl3): δ=8.61 (s, 2H);
[0059] 13 C NMR (400MHz, CDCl3): δ=154.12, 129.97, 114.80, 114.11;
[0060] The NMR results showed that compound 2 was successfully synthesized.
[0061] (2) Synthesis of Compound 3
[0062] Compound 2 (2.4 g, 12.9 mmol), acetic acid (30 mL), water (20 mL), and concentrated hydrochloric acid (30 mL, 37% HCl, 363 mmol) obtained in step (1) were added to a round-bottom flask to form a mixed solution. The mixed solution was stirred at 130 ° C for 32 h. After removing the solvent, acetone was added to dissolve the product. Filter by suction and collect the filtrate. After removing the solvent, dry to obtain a light yellow solid (2.19 g, yield 75.8%), which is compound 3.
[0063] The molecular structure of compound 3 was determined using a nuclear magnetic resonance spectrometer, specifically including: dissolving compound 3 in deuterated dimethyl sulfoxide (DMSO-d6) and filling it into a nuclear magnetic resonance tube for testing. The results are as follows:
[0064] 1H NMR (400MHz, DMSO-d6): δ=13.55 (s, 2H), 8.40 (s, 2H);
[0065] 13C NMR (400MHz, DMSO-d6): δ=167.74, 153.89, 133.88, 121.99;
[0066] The NMR results showed that compound 3 was successfully synthesized.
[0067] (3) Synthesis of Compound 4
[0068] Compound 3 (3.5 g, 15.6 mmol) obtained in step (2), anhydrous toluene (50 mL), and trifluoroacetic anhydride (15 mL, 108 mmol) were added to a round-bottom flask to form a mixed solution. The mixed solution was stirred at 40 ° C for 10 h. After cooling, water was slowly added dropwise and stirred for 15 min. The crude product was extracted with dichloromethane, and after removing the solvent, it was dried to obtain a light yellow solid (1.82 g, yield 56.5%), which is compound 4.
[0069] The molecular structure of compound 4 was determined using a nuclear magnetic resonance spectrometer, specifically including: dissolving compound 4 in deuterated dimethyl sulfoxide (DMSO-d6) and filling it into a nuclear magnetic resonance tube for testing. The results are as follows:
[0070] 1 H NMR (400MHz, DMSO-d6): δ = 8.95 (s, 2H);
[0071] 13 C NMR (400MHz, DMSO-d6): δ=162.42, 156.36, 130.19, 120.51;
[0072] The NMR results indicated that compound 4 was successfully synthesized.
[0073] (4) Synthesis of Compound 5
[0074] Step 1: Add compound 4 (1.0 g, 4.85 mmol) and 1,4-dioxane (60 mL) to a round-bottom flask. Add ethyl (triphenylphosphine) acetate (1.86 g, 5.34 mmol) in batches within 30 min to form a mixed solution. Stir the mixed solution at 85 ° C for 6 h. After removing the solvent, dry it to obtain a light brown solid, which is compound 4-1.
[0075] The molecular structure of compound 4-1 was determined using a nuclear magnetic resonance spectrometer, specifically including: dissolving compound 4-1 in deuterated chloroform (CDCl3) and filling it into a nuclear magnetic resonance tube for testing. The results are as follows:
[0076] 1 H NMR (400MHz, CDCl3): δ=9.91 (s, 1H), 8.68 (s, 1H), 6.28 (s, 1H), 4.35 (q, J=7.2Hz, 2H), 1.39 (t, J=7.1Hz, 3H);
[0077] The NMR results showed that compound 4-1 was successfully synthesized.
[0078] Step 2: Add compound 4-1, methanol (20 mL), and a methanol solution of sodium methoxide (1.08 mL, 5.4 M, 5.8 mmol) into a round-bottom flask to form a mixed solution. Stir the mixed solution at 65°C for 5 h. Filter by suction, wash the filter cake with methanol, and dry to obtain a yellow solid, which is compound 4-2.
[0079] Step 3: Add compound 4-2, acetonitrile (30 mL), and concentrated hydrochloric acid (0.4 mL, 37% HCl, 4.84 mmol) to a round-bottom flask to form a mixed solution. Stir the mixed solution at room temperature for 0.5 h. Filter by suction, wash the filter cake with acetonitrile, and air-dry to obtain a light yellow solid, which is compound 4-3.
[0080] The molecular structure of compound 4-3 was determined using a nuclear magnetic resonance spectrometer, specifically including: dissolving compound 4-3 in deuterated dimethyl sulfoxide (DMSO-d6) and filling it into a nuclear magnetic resonance tube for testing. The results are as follows:
[0081] 1 H NMR (400MHz, DMSO-d6): δ=9.83 (s, 1H), 7.92 (s, 2H), 4.13 (q, J=7.1Hz, 2H), 1.23 (t, J=7.1Hz, 3H);
[0082] The NMR results showed that compound 4-3 was successfully synthesized.
[0083] Step 4: Add compound 4-3 and anhydrous acetonitrile (80 mL) to a round-bottom flask to form a mixed solution. The mixed solution was stirred at 90 ° C for 20 h. Filtered and the filtrate was collected. After removing the solvent, the filter cake was washed with isopropanol and dried to obtain a reddish brown solid (0.55 g, yield 55.5%), which is compound 5.
[0084] The molecular structure of compound 5 was determined using a nuclear magnetic resonance spectrometer, specifically including: dissolving compound 5 in deuterated chloroform (CDCl3) and filling it into a nuclear magnetic resonance tube for testing. The results are as follows:
[0085] 1 H NMR (400MHz, CDCl3): δ=8.67 (s, 2H), 3.49 (s, 2H);
[0086] 13 C NMR (400MHz, CDCl3): δ=196.28, 157.45, 140.86, 117.84, 47.64;
[0087] The NMR results indicated that compound 5 was successfully synthesized.
[0088] (5) Synthesis of Compound 6
[0089] Compound 5 (50 mg, 0.245 mmol), malononitrile (32.4 mg, 0.490 mmol), chlorobenzene (10 mL), pyridine (0.3 mL), and titanium tetrachloride (0.3 mL) were added to a round-bottom flask to form a mixed solution. The mixed solution was stirred at 50 ° C for 6 h. After cooling, it was poured into water, and the crude product was extracted with chloroform. After removing the solvent, the crude product was dissolved in an appropriate amount of chloroform, precipitated with petroleum ether, and filtered, and repeated twice. The filter cake was dried to obtain a brown solid (15 mg, yield 24.3%), which is compound 6.
[0090] The molecular structure of compound 6 was determined using a nuclear magnetic resonance spectrometer, specifically including: dissolving compound 6 in deuterated chloroform (CDCl3) and filling it into a nuclear magnetic resonance tube for testing. The results are as follows:
[0091] 1 H NMR (400MHz, CDCl3): δ=9.42 (s, 1H), 8.65 (s, 1H), 3.96 (s, 2H);
[0092] The molecular structure of compound 6 was determined using a quadrupole time-of-flight (QTOF) mass spectrometer (MS), specifically including: dissolving compound 6 in chloroform in the form of a dilute solution, depositing an appropriate amount on the stage, and testing after air-drying the solvent. The results are as follows:
[0093] MS(Q TOF): Cald for C 12 H4N4OS(M + ): 252.25, Found: 251.00;
[0094] NMR and mass spectrometry results indicated that compound 6 was successfully synthesized.
[0095] (6) Synthesis of Compound 8
[0096] Compound 7 (93 mg, 0.080 mmol), compound 6 (20 mg, 0.079 mmol), chloroform (20 mL), acetic anhydride (0.8 mL), and boron trifluoride etherate (0.4 mL) were added to two round-bottom flasks to form a mixed solution. The mixed solution was stirred at 60 ° C for 3 h. After cooling, methanol was slowly added and stirred for 15 min. Filtered, the filter cake was washed with methanol, and purified by column (eluent was petroleum ether: dichloromethane = 1:1, v / v) to obtain a green solid (46 mg, 41.2%), which was compound 8.
[0097] The molecular structure of compound 8 was determined using a nuclear magnetic resonance spectrometer, specifically including: dissolving compound 8 in deuterated chloroform (CDCl3) and filling it into a nuclear magnetic resonance tube for testing. The results are as follows:
[0098] 1 H NMR (400MHz, CDCl3): δ=10.14 (s, 1H), 9.39 (s, 1H), 9.28 (s, 1H), 8.49 (s, 1H), 4.71 (dd, J=36.8, 7.9Hz, 4H), 3.18(dd, J=43.0, 7.5Hz, 4H), 2.14-2.04(m, 4H), 1.43-1.36(m, 8H), 1.31-0.82(m, 68H), 0.69-0.62(m, 12H);
[0099] The NMR results indicated that compound 8 was successfully synthesized.
[0100] (7) Synthesis of BTC-1
[0101] Compound 8 (50 mg, 0.036 mmol), compound 9 (11 mg, 0.042 mmol), anhydrous toluene (20 mL), acetic anhydride (0.8 mL), and boron trifluoride etherate (0.4 mL) were added to two round-bottom flasks to form a mixed solution. The mixed solution was stirred at 60 ° C for 2 h. After cooling, methanol was slowly added and stirred for 15 min. Filtered by suction, the filter cake was washed with methanol, and purified by column (eluent was petroleum ether: dichloromethane = 1: 3, v / v) to obtain a black solid (49 mg, 83.4%), which was compound BTC-1.
[0102] The molecular structure of compound BTC-1 was determined using a nuclear magnetic resonance spectrometer, specifically including: dissolving compound BTC-1 in deuterated chloroform (CDCl3) and filling it into a nuclear magnetic resonance tube for testing. The results are as follows:
[0103] 1 H NMR (400MHz, CDCl3): δ=9.40 (s, 1H), 9.29 (s, 1H), 9.17 (s, 1H), 8.80 (s, 1H), 8.50 (s, 1H), 7.96 (s, 1H), 4.78 (t, J=7.7Hz, 4H), 3 .21(dd, J=18.4, 7.7Hz, 4H), 2.17-2.07(m, 4H), 1.52-1.44(m, 4H), 1.40-1.36(m, 4H), 1.28-0.82(m, 68H), 0.71-0.64(m, 12H);
[0104] The molecular structure of compound BTC-1 was determined using a matrix-assisted laser desorption ionization time-of-flight (MALDI TOF) mass spectrometer (MS), specifically including: dissolving compound BTC-1 in chloroform in the form of a dilute solution, depositing an appropriate amount on the stage, and testing after air-drying the solvent. The results are as follows:
[0105] MS (MALDI TOF): Cald for C 92 H 106 C 12 N 10 O2S6(M + ): 1647.19, Found: 1647.07;
[0106] The results of NMR and mass spectrometry showed that compound BTC-1 was successfully synthesized. Figure 2 As shown in BTC-1.
[0107] (8) Synthesis of BTC-2
[0108] Compound 7 (107 mg, 0.092 mmol), compound 6 (58 mg, 0.230 mmol), chloroform (30 mL), acetic anhydride (1.6 mL) and boron trifluoride etherate (0.8 mL) were added to two round-bottom flasks to form a mixed solution. The mixed solution was stirred at 60 ° C for 10 h. After cooling, methanol was slowly added and stirred for 15 min. Filtered by suction, the filter cake was washed with methanol, and purified by column (eluent: petroleum ether: dichloromethane = 1:4, v / v) to obtain a black solid (47 mg, 31.3%), which is compound BTC-2.
[0109] The molecular structure of compound BTC-2 was determined using a nuclear magnetic resonance spectrometer, specifically including: dissolving compound BTC-2 in deuterated chloroform (CDC13) and filling it into a nuclear magnetic resonance tube for testing. The results are as follows:
[0110] 1 H NMR (400MHz, CDCl3): δ=9.41 (s, 2H), 9.30 (s, 2H), 8.51 (s, 2H), 4.81 (d, J=7.3Hz, 4H), 3.23 (d, J=7.6Hz , 4H), 2.17-2.09(m, 4H), 1.53-1.47(m, 4H), 1.42-1.39(m, 4H), 1.25-0.83(m, 68H), 0.72-0.66(m, 12H);
[0111] The molecular structure of compound BTC-2 was determined using a matrix-assisted laser desorption ionization time-of-flight (MALDI TOF) mass spectrometer (MS), specifically including: dissolving compound BTC-2 in chloroform in the form of a dilute solution, depositing an appropriate amount on the stage, and testing after air-drying the solvent. The results are as follows:
[0112] MS (MALDI TOF): Cald for C 92 H 106 N 12 O2S7(M + ): 1636.36, Found: 1636.14;
[0113] The results of NMR and mass spectrometry showed that compound BTC-2 was successfully synthesized. Figure 2 As shown in BTC-2.
[0114] (9) Synthesis of BTC-3
[0115] Compound 8 (50 mg, 0.036 mmol), compound 10 (10 mg, 0.043 mmol), anhydrous toluene (20 mL), acetic anhydride (0.8 mL) and boron trifluoride etherate (0.4 mL) were added to two round-bottom flasks to form a mixed solution. The mixed solution was stirred at 60 ° C for 2 h. After cooling, methanol was slowly added and stirred for 15 min. Filtered by suction, the filter cake was washed with methanol, and purified by column (eluent was petroleum ether: dichloromethane = 1: 2, v / v) to obtain a black solid (48 mg, 83.4%), which was compound BTC-3.
[0116] The molecular structure of compound BTC-3 was determined using a nuclear magnetic resonance spectrometer, specifically including: dissolving compound BTC-3 in deuterated chloroform (CDCl3) and filling it into a nuclear magnetic resonance tube for testing. The results are as follows:
[0117] 1 H NMR (400MHz, CDCl3): δ=9.39 (s, 1H), 9.28 (s, 1H), 9.16 (s, 1H), 8.57 (dd, J=9.9, 6.4Hz, 1H), 8.50 (s, 1H), 7.70 (t, J=7.5Hz, 1H), 4.78 (t, J= 7.9Hz, 4H), 3.20 (dd, J=12.4, 7.6Hz, 4H), 2.16-2.06 (m, 4H), 1.53-1.44 (m, 4H), 1.39-1.37 (m, 4H), 1.28-0.82 (m, 68H), 0.70-0.65 (m, 12H);
[0118] The molecular structure of compound BTC-3 was determined using a matrix-assisted laser desorption ionization time-of-flight (MALDI TOF) mass spectrometer (MS), specifically including: dissolving compound BTC-3 in chloroform in the form of a dilute solution, depositing an appropriate amount on the stage, and testing after air-drying the solvent. The results are as follows:
[0119] MS (MALDI TOF): Cald for C 92 H 106 F2N 10 O2S6(M + ): 1614.28, Found: 1613.97;
[0120] The results of NMR and mass spectrometry showed that compound BTC-3 was successfully synthesized. Figure 2 As shown in BTC-3.
[0121] Figure 3 The cyclic voltammetry test curves of BTC-1, BTC-2 and BTC-3 are shown in Figure 2. The results show that the LUMO energy level of BTC-1 measured by the cyclic voltammetry (CV) method is -3.97eV, the HOMO energy level is -5.78eV, and the corresponding electrochemical band gap is 1.81eV; the LUMO energy level of BTC-2 is -4.03eV, the HOMO energy level is -5.81eV, and the corresponding electrochemical band gap is 1.78eV; the LUMO energy level of BTC-3 is -3.98eV, the HOMO energy level is -5.76eV, and the corresponding electrochemical band gap is 1.78eV.
[0122] Figure 4 The following are the UV-visible absorption spectra of BTC-1, BTC-2 and BTC-3. The results show that in the thin film state, the maximum absorption peak of BTC-1 is at 869nm, the absorption band edge is 950nm, and the optical band gap is 1.31eV; the maximum absorption peak of BTC-2 is at 900nm, the absorption band edge is 1000nm, and the optical band gap is 1.24eV; the maximum absorption peak of BTC-3 is at 858nm, the absorption band edge is 960nm, and the optical band gap is 1.29eV.
[0123] Example 2
[0124] The organic solar cell assembly is performed based on the synthesized electron acceptor BTC-1, which specifically includes the following steps:
[0125] (1) Anode: The transparent conductive glass with strips of ITO (anode) etched on the surface was cleaned with a cleaning agent, deionized water, acetone, and isopropanol ultrasonic oscillation in sequence, dried, and then treated with ultraviolet ozone for 10 minutes;
[0126] (2) Anode modification layer: A 2PACz transport layer was spin-coated on the conductive glass surface using a 0.22 mg / mL 2PACz methanol solution, and then annealed at 100 °C for 10 min;
[0127] (3) Active layer: Before spin coating the active layer, a PM6:BTC-1 chloroform solution with a mass ratio of 1:1.2 and a total concentration of 16 mg / mL was prepared, and 0.25% of 1,8-diiodooctane (DIO) was added as an additive. After stirring and dissolving at 60°C for 1 hour, spin coating was performed at a speed of 4000 rpm to obtain an active layer of about 100 nm. Then, annealing was performed at 90°C for 5 minutes.
[0128] (4) Cathode modification layer: On the active layer prepared in step (3), a PDINN transport layer was spin-coated using a 1.5 mg / mL PDINN methanol solution.
[0129] (5) Cathode: Based on step (4), a 100 nm thick Ag electrode is deposited by evaporation, thereby obtaining an effective area of 6 mm 2 The organic solar cell is PM6:BTC-1 and the test area is 4.572mm 2 .
[0130] At a light intensity of 100 mW / cm 2 The current-voltage curve of PM6:BTC-1 device was tested under AM1.5 simulated sunlight. The results are as follows Figure 5 The results show that the open circuit voltage of PM6:BTC-1 device is 0.765V and the short circuit current density is 25.51mA / cm 2 , the filling factor is 73.35% and the power conversion efficiency (PCE) is 14.33%.
[0131] Comparative Example 1
[0132] Organic solar cells were assembled based on the synthesized electron acceptor BTC-2, and the specific steps were the same as those in Example 2, except that: the electron acceptor selected BTC-2 to be assembled into a PM6:BTC-2 device.
[0133] At a light intensity of 100 mW / cm 2 The current-voltage curve of PM6:BTC-2 device was tested under AM1.5 simulated sunlight. The results are as follows Figure 5 The results show that the open circuit voltage of PM6:BTC-2 device is 0.722V and the short circuit current density is 30.34mA / cm 2 , the filling factor is 78.39% and the power conversion efficiency (PCE) is 17.17%.
[0134] Comparative Example 2
[0135] Organic solar cells were assembled based on the synthesized electron acceptor BTC-3, and the specific steps were the same as those in Example 2, except that: the electron acceptor selected BTC-3 to be assembled into a PM6:BTC-3 device.
[0136] At a light intensity of 100 mW / cm 2 The current-voltage curve of PM6:BTC-3 device was tested under AM1.5 simulated sunlight. The results are as follows Figure 5 The results show that the open circuit voltage of the PM6:BTC-3 device is 0.773V and the short circuit current density is 27.76mA / cmm 2 , the filling factor is 77.37% and the power conversion efficiency (PCE) is 16.60%.
[0137] Example 3
[0138] The semi-transparent organic solar cell assembly is performed based on the synthesized electron acceptor BTC-2, which specifically includes the following steps:
[0139] (1) Anode: The transparent conductive glass with strips of ITO (anode) etched on the surface was cleaned with a cleaning agent, deionized water, acetone, and isopropanol ultrasonic oscillation in sequence, dried, and then treated with ultraviolet ozone for 10 minutes;
[0140] (2) Anode modification layer: A 2PACz transport layer was spin-coated on the conductive glass surface using a 0.22 mg / mL 2PACz methanol solution, and then annealed at 100 °C for 10 min;
[0141] (3) Active layer: Before spin coating the active layer, a PM6:BTC-2 chloroform solution with a mass ratio of 1:1.2 and a total concentration of 13 mg / mL was prepared, and 0.25% of 1,8-diiodooctane (DIO) was added as an additive. After stirring and dissolving at 60°C for 1 hour, spin coating was performed at a speed of 2500 rpm to obtain an active layer of about 60 nm. Then, annealing was performed at 90°C for 5 minutes.
[0142] (4) Cathode modification layer: On the active layer prepared in step (3), a PDINN transport layer was spin-coated using a 1.5 mg / mL PDINN methanol solution.
[0143] (5) Cathode: Based on step (4), a 12 nm Ag electrode is deposited by evaporation, thereby obtaining an effective area of 6 mm 2 Semi-transparent organic solar cell with a size of 12nm and a test area of 4.76mm 2 .
[0144] At a light intensity of 100 mW / cm 2 The current-voltage curve of the device was tested under AM1.5 simulated sunlight. The results are as follows Figure 6 The results show that the open circuit voltage of the 12nm device is 0.72V and the short circuit current density is 22.28mA / cm 2 , the filling factor is 75.09%, the power conversion efficiency (PCE) is 11.96%, the average light transmittance (APT) is 24.86%, and the light utilization efficiency (LUE) is 2.97% (LUE = PCE × APT).
[0145] Comparative Example 4
[0146] Semi-transparent organic solar cells were assembled based on the synthesized electron acceptor BTC-2. The specific steps were the same as those in Example 3, except that the thickness of the cathode Ag electrode was 14 nm, and the devices were assembled into devices numbered 14 nm.
[0147] At a light intensity of 100 mW / cm 2 The current-voltage curve of the device was tested under AM1.5 simulated sunlight. The results are as follows Figure 6 The results show that the open circuit voltage of the 14nm device is 0.71V and the short circuit current density is 23.54mA / cm 2 , the filling factor is 74.56%, the power conversion efficiency (PCE) is 12.43%, the average light transmittance (APT) is 22.76%, and the light utilization efficiency (LUE) is 2.83%.
[0148] Comparative Example 5
[0149] Semi-transparent organic solar cells were assembled based on the synthesized electron acceptor BTC-2. The specific steps were the same as those in Example 3, except that the thickness of the cathode Ag electrode was 16 nm, and the devices were assembled into devices numbered 16 nm.
[0150] At a light intensity of 100 mW / cm 2 The current-voltage curve of the device was tested under AM1.5 simulated sunlight. The results are as follows Figure 6 The results show that the open circuit voltage of the 16nm device is 0.71V and the short circuit current density is 23.73mA / cm 2 , the filling factor is 75.33%, the power conversion efficiency (PCE) is 12.67%, the average light transmittance (APT) is 21.41%, and the light utilization efficiency (LUE) is 2.71%.
[0151] Comparative Example 6
[0152] Semi-transparent organic solar cells were assembled based on the synthesized electron acceptor BTC-2. The specific steps were the same as those in Example 3, except that the thickness of the cathode Ag electrode was 12 nm, and a 45 nm TeO2 optical layer was evaporated on the Ag electrode to assemble a device numbered 12 nm + TeO2.
[0153] At a light intensity of 100 mW / cm 2 The current-voltage curve of the device was tested under AM1.5 simulated sunlight. The results are as follows Figure 6 The results show that the open circuit voltage of the device numbered 12nm+TeO2 is 0.70V and the short circuit current density is 20.39mA / cm 2 , the filling factor is 72.11%, the power conversion efficiency (PCE) is 10.31%, the average light transmittance (APT) is 35.19%, and the light utilization efficiency (LUE) is 3.63%.
[0154] Comparative Example 7
[0155] Semi-transparent organic solar cells were assembled based on the synthesized electron acceptor BTC-2. The specific steps were the same as those in Example 3, except that the thickness of the cathode Ag electrode was 14 nm, and a 45 nm TeO2 optical layer was evaporated on the Ag electrode to assemble a device numbered 14 nm + TeO2.
[0156] At a light intensity of 100 mW / cm 2 The current-voltage curve of the device was tested under AM1.5 simulated sunlight. The results are as follows Figure 6 The results show that the open circuit voltage of the device numbered 14nm+TeO2 is 0.70V and the short circuit current density is 21.07mA / cm 2 , the filling factor is 74.65%, the power conversion efficiency (PCE) is 11.06%, the average light transmittance (APT) is 32.03%, and the light utilization efficiency (LUE) is 3.54%.
[0157] Comparative Example 8
[0158] Semi-transparent organic solar cells were assembled based on the synthesized electron acceptor BTC-2. The specific steps were the same as those in Example 3, except that the thickness of the cathode Ag electrode was 16 nm, and a 45 nm TeO2 optical layer was evaporated on the Ag electrode to assemble a device numbered 16 nm + TeO2.
[0159] At a light intensity of 100 mW / cm 2 The current-voltage curve of the device was tested under AM1.5 simulated sunlight. The results are as follows Figure 6The results show that the open circuit voltage of the device numbered 16nm+TeO2 is 0.70V and the short circuit current density is 21.45mA / cm 2 , the filling factor is 75.41%, the power conversion efficiency (PCE) is 11.34%, the average light transmittance (APT) is 30.15%, and the light utilization efficiency (LUE) is 3.42%.
[0160] Example 4
[0161] The semi-transparent organic solar cell assembly is performed based on the synthesized electron acceptor BTC-2, which specifically includes the following steps:
[0162] (1) Anode: The transparent conductive glass with strips of ITO (anode) etched on the surface was cleaned with a cleaning agent, deionized water, acetone, and isopropanol ultrasonic oscillation in sequence, dried, and then treated with ultraviolet ozone for 10 minutes;
[0163] (2) Anode modification layer: A 2PACz transport layer was spin-coated on the conductive glass surface using a 0.22 mg / mL 2PACz methanol solution, and then annealed at 100 °C for 10 min;
[0164] (3) Active layer: Before spin coating the active layer, a PM6:BTC-2 chloroform solution with a mass ratio of 1:1.2 and a total concentration of 13 mg / mL was prepared, and 0.25% of 1,8-diiodooctane (DIO) was added as an additive. After stirring and dissolving at 60°C for 1 hour, spin coating was performed at a speed of 3500 rpm to obtain an active layer of about 50 nm. Then, annealing was performed at 90°C for 5 minutes.
[0165] (4) Cathode modification layer: On the active layer prepared in step (3), a PDINN transport layer was spin-coated using a 1.5 mg / mL PDINN methanol solution.
[0166] (5) Cathode: Based on step (4), a 12nm thick Ag electrode is deposited by evaporation, and then a 45nm thick TeO2 optical layer is deposited. Thus, an effective area of 6mm is obtained. 2 Semi-transparent organic solar cell, numbered 1:1.2, test area 4.76mm 2 .
[0167] At a light intensity of 100 mW / cm 2 Under the AM1.5 simulated sunlight, the current-voltage curve of the device with the test number of 1:1.2 is as follows Figure 7 The results show that the open circuit voltage of the device numbered 1:1.2 is 0.71V and the short circuit current density is 18.52mA / cm 2, the filling factor is 74.37%, the power conversion efficiency (PCE) is 9.78%, the average light transmittance (APT) is 34.86%, and the light utilization efficiency (LUE) is 3.41%.
[0168] Comparative Example 9
[0169] Semi-transparent organic solar cells were assembled based on the synthesized electron acceptor BTC-2. The specific steps were the same as those in Example 4, except that before spin coating the active layer, a PM6:BTC-2 chloroform solution with a mass ratio of 1:1.6 between the electron donor and the electron acceptor and a total concentration of 13 mg / mL was prepared.
[0170] At a light intensity of 100 mW / cm 2 Under the AM1.5 simulated sunlight, the current-voltage curve of the device with the test number of 1:1.2 is as follows Figure 7 The results show that the open circuit voltage of the device numbered 1:1.6 is 0.72V and the short circuit current density is 19.58mA / cm 2 , the filling factor is 74.17%, the power conversion efficiency (PCE) is 10.39%, the average light transmittance (APT) is 43.51%, and the light utilization efficiency (LUE) is 4.52%.
[0171] Comparative Example 10
[0172] Semi-transparent organic solar cells were assembled based on the synthesized electron acceptor BTC-2. The specific steps were the same as those in Example 4, except that before spin coating the active layer, a PM6:BTC-2 chloroform solution with a mass ratio of 1:2.0 between the electron donor and the electron acceptor and a total concentration of 13 mg / mL was prepared.
[0173] At a light intensity of 100 mW / cm 2 Under the AM1.5 simulated sunlight, the current-voltage curve of the device with the test number of 1:2.0 is as follows Figure 7 The results show that the open circuit voltage of the device numbered 1:2.0 is 0.71V and the short circuit current density is 19.80mA / cm 2 , the filling factor is 75.18%, the power conversion efficiency (PCE) is 10.56%, the average light transmittance (APT) is 46.20%, and the light utilization efficiency (LUE) is 4.88%.
Claims
1. An ultra-narrow bandgap electron acceptor, characterized in that: The ultra-narrow bandgap electron acceptor comprises a symmetrical acceptor with a benzothiadiazole ladder-shaped fused ring structure as the core and both ends being benzothiadiazole derivative ends; or, The core of the invention is a benzothiadiazole ladder-shaped condensed ring structure, one end of which is a benzothiadiazole derivative terminal, and the other end of which is an asymmetric receptor of a cyanoindanone terminal.
2. The ultra-narrow bandgap electron acceptor according to claim 1, characterized in that: The cyanoindanone terminal is at least one of the following chemical structural formulas:
3. An active layer comprising an electron acceptor and an electron donor, wherein the electron donor is a wide bandgap polymer donor material, characterized in that: The electron acceptor is the ultra-narrow band gap electron acceptor according to claim 1 or 2.
4. The active layer according to claim 3, characterized in that The weight ratio of the electron donor to the electron acceptor is 1:2 to 2:1, and the thickness of the active layer is 50 to 300 nm.
5. A method for preparing an active layer according to claim 3 or 4, characterized in that: The active layer is prepared by forming a mixed solution of an electron acceptor, an electron donor and an additive into a film and then subjecting the film to annealing treatment.
6. The method for preparing the active layer according to claim 5, characterized in that: The additive is 1,8-diiodooctane or chloronaphthalene, and the volume of the additive is 0.1-5% of the volume of the mixed solution of the electron acceptor and the electron donor.
7. The method for preparing an active layer according to claim 5, characterized in that: The annealing temperature of the annealing treatment is 80-200° C., and the annealing time is 5-30 minutes.
8. An organic solar cell comprising the active layer according to claim 3 or 4.
9. The organic solar cell according to claim 8, comprising a substrate, an anode, an anode modification layer, an active layer, a cathode modification layer and a cathode, characterized in that: The substrate is glass; the anode is ITO or FTO; the anode modification layer is 2PACz, PEDOT:PSS or MoO3; the electron donor in the active layer is PM6 or D18, and the electron acceptor is BTC-1, BTC-2 or BTC-3; the cathode modification layer is PDINN, PFN-Br or ZnO; and the cathode is Ag.
10. The organic solar cell according to claim 9, characterized in that The thickness of the cathode Ag is 10nm-100nm, and an optical layer is modified on the cathode Ag.
Citation Information
Patent Citations
Benzothiadiazole deuterated derivative and application thereof in organic electronic device
CN113087725A
Semiconductor mixed material and application thereof
CN113571639A
Siloxane group-containing A-DA 'D-A type conjugated organic small molecule as well as preparation method and application thereof
CN114773380A
Method for patterning semiconductor layer
CN117580423A
Novel compound and organic electronic device using same
WO2021107674A1